INTEGRATED PRODUCTION OPTIMIZATION AT DEPLETED GAS FIELD - FAJAR KURNIAWAN (NIM 12204059), IMRON
X field is a giant gas field which has depleted. Nowadays, the recovery factor is exceeded 80% with the ultimate recovery factor at about 96.75%. The reservoir pressure has dropped to around 500 psi. Due to this low reservoir pressure, it needs a production optimization strategy to withdraw the remaining reserve at optimum rate. For this purpose, it needs an integrated study from some discipline to analyze the appropriate strategy for production optimization. Here, we make a study by integrating Production and Reservoir engineering to get the best strategy. Acidizing, increasing tubing diameter, reperforations, surface facilities optimization, and pressure maintenance is choices of the strategy. Due to the lack of data, this paper just investigate about acidizing and pulling out the 7 inch tubing at 9? inch casing diameter (producing directly from 9? inch casing). Here, we will use sets data of 9 wells in this field which represents each cluster. The result of our study indicates that acidizing is the most optimal strategy. Acidizing to a well with skin=1will increasing the production rate as much as 20% while a well with skin=16.5 the production rate will increase as much as 250%. Pulling out 7 inch tubing just give a little effect into performance of the well. The well with the initial rate at 2.2 MMscfd will increase the production rate as much as 0.6% when the tubing have pulled out. While the well with 27 MMscfd initial rate will give as much as 12.5% increasing rate.